Expert System Implementation of the Certainty Factor Method for Smartphone Damage Diagnosis - Syahrul Mubarak Abdullah; Andi Syarifuddin; Ahmed Saeed Alghamdi; Hariani Ma'tang Pakka (Universitas Khairun, 2024)
Android smartphone is currently one of the most extensively utilized operating systems. Nevertheless, Android devices are susceptible to issues such as Ic Emmc, Ic Power, software malfunctions, Blank Screen, Hang, complete device malfunction, and boot loop. Prompt intervention is crucial when a smartphone experiences a problem to prevent more harm and safeguard the user. The Certainty Factor (CF) accounts for the inherent uncertainty in an expert's analysis. Expressions such as